2011
DOI: 10.1038/ismej.2011.70
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic analysis of autonomously collected and preserved marine bacterioplankton

Abstract: Planktonic microbial activity and community structure is dynamic, and can change dramatically on time scales of hours to days. Yet for logistical reasons, this temporal scale is typically undersampled in the marine environment. In order to facilitate higher-resolution, long-term observation of microbial diversity and activity, we developed a protocol for automated collection and fixation of marine microbes using the Environmental Sample Processor (ESP) platform. The protocol applies a preservative (RNALater) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 65 publications
4
110
0
Order By: Relevance
“…The TonB system transports large molecules (e.g., polysaccharides, proteins, and siderophores) in through the outer membrane of Gram-negative bacteria. Its importance in marine environments is evidenced by the presence of these genes in marine bacterial genomes and pelagic metagenomes (29-31), their high levels of expression in metatranscriptome data (32), and the proteomic identification of their products as the predominant membrane proteins in pelagic bacteria (33). In this study, they accounted for nearly 1% of gene function annotations at some high-nutrient sites (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…The TonB system transports large molecules (e.g., polysaccharides, proteins, and siderophores) in through the outer membrane of Gram-negative bacteria. Its importance in marine environments is evidenced by the presence of these genes in marine bacterial genomes and pelagic metagenomes (29-31), their high levels of expression in metatranscriptome data (32), and the proteomic identification of their products as the predominant membrane proteins in pelagic bacteria (33). In this study, they accounted for nearly 1% of gene function annotations at some high-nutrient sites (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Several previous metagenomic and metatranscriptomic studies had indicated that bacterial populations with high genetic relatedness to HTCC2255 (X95% average amino acid identity) were consistently present at this site (DeLong, 2005;Ottesen et al, 2011;Rich et al, 2011). We therefore retrieved DMSP gene sequences from the available Monterey Bay metagenomic data sets (Rich et al, 2011) and designed species-specific PCR assays that could be employed on the ESP to characterize gene dynamics over time.…”
Section: Roseobacter Htcc2255 Dmsp Genes In Monterey Baymentioning
confidence: 99%
“…In the coastal upwelling system of Monterey Bay, CA, previous metagenomic and metatranscriptomic surveys indicated consistent and abundant populations of a bacterial taxon with high genetic relatedness to Roseobacter strain HTCC2255 (Ottesen et al, 2011), a bacterium capable of both DMSP cleavage and demethylation (Newton et al, 2010). We took advantage of the predictable presence of this bacterium to design HTC2255-specific PCR primers for in situ observations for the first committed step in each of the two DMSP degradation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…in situ (15,17,(44)(45)(46). For example, analysis of metatranscriptomic data of bacterioplankton from the Monterey Bay of California showed that the TMAO transporter is one of the most highly expressed transporters in the MRC representative, Rhodobacterales sp.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-binding cassette (ABC) transporters form one of the largest gene superfamilies found within many bacterial genomes (14), and their expression is frequently detected in the marine environment (15)(16)(17). ABC transporters are essential for bacteria because they are responsible for the uptake of a wide range of compounds, such as sugars, amino acids, metals, and vitamins, at the expense of ATP (18).…”
mentioning
confidence: 99%